The Development of Training Curriculum to Strengthen Working Human Relations at Work for Student Council Leader of Student in Secondary School under the Office of Nakhonphanom Provincial Educational Service Area 2 - Udomkan, Wongtawat; Steannoppakao, Pornthep; Phengsawat, Waro (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
The objectives of the research article were 1) to develop training courses for enhancing human relations in work. For junior high school student council leaders, 2) to evaluate the effectiveness of training courses to strengthen human relations in the workplace. For junior high school student council leaders Schools under the Office of Nakhon Phanom Primary Educational Service Area 2. The sample groups were Leaders of the Junior High School Student Council, Ban Kam NokKok School and Ban Don Klang School Nakhon Phanom Primary Educational Service Area Office, District 2, 40 people. The research instruments were the Development of Training Curriculum to Strengthen Working Human Relations at work for student council leader of student in Secondary School under the Office of Nakhonphanom Provincial Educational Service Area 2. The statistics used for data analysis were mean, standard deviation and test statistics. The result of this research found that: 1. The results of the development of training courses for enhancing human relations in work For the junior high school student council leaders, it was found that the content consisted of 1)lead well (cooperate with relevant people) 2)join together, help build (Providing assistance for collaborators) 3)international language (smiling and friendly for) 4)precedent behavior (Always be persistent and respectful) 5)Acknowledge (Honor and give opportunities to join work or become a democracy). 2. The results of the evaluation of the effectiveness of the training courses to strengthen the working human relations for the junior high school student council leaders, it was found that found that 1) the trainees had knowledge Interpersonal understanding for junior high school student council leaders after training was statistically significantly higher than before training at the .01 level. 2) Score on interpersonal skills of junior high school students Overall, it was at a very good level according to the hypothesis. 3) Overall student satisfaction with the training program was at the highest level higher than the hypothesis and to make the training course more complete Researchers have adjusted some of the learning activities to be simpler and more practical. Adding practice activities taking more action to give student council leaders the skills and interpersonal skills they need to work together.